The effectiveness of the Security Council in applying the rules of international humanitarian law. - Sawalha, Muchir; Filali, Kamel (Journal of Human Sciences, 2022)
The rules of international human law aim to limit attacks against civilians in addition to hostilities, and reduce the use of indiscriminate means of combat, and prevent all manifestations of killing, violence, rape, and family dispersal and displacement. This can only be achieved through the contribution and role of the Security Council in implementing these rules and recognition of wide powers, jurisdictions and powers in resolving international disputes and achieving international peace and security.